2020
DOI: 10.1200/jco.2020.38.6_suppl.225
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors that affect survival outcomes in men with metastatic castration-resistant prostate cancer (mCRPC) treated with radium-223.

Abstract: 225 Background: Radium-223 (Ra-223) improved overall survival (OS) in men with mCRPC with predominantly bone metastases. We analyzed their survival outcomes to identify factors associated with prognosis for men treated with Ra-223. Methods: This was a retrospective study of men with mCRPC at Princess Margaret Cancer Centre treated with Ra-223. Demographics, disease characteristics, number of bone metastasis [ < 6, 6-20, > 20], laboratory results, number of Ra-223 doses, systemic treatment lines after ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…No statistically significant correlation was found in our study between discontinuation of Ra-223 due to toxicity and number of metastases, PS, baseline PSA, ALP and NLR despite in previous studies these variables have been shown to correlate with OS. 13,17,20,22,23,25 Of course, the limited sample size of our series could imply a significant risk of false negative results in the analysis of single prognostic factors.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…No statistically significant correlation was found in our study between discontinuation of Ra-223 due to toxicity and number of metastases, PS, baseline PSA, ALP and NLR despite in previous studies these variables have been shown to correlate with OS. 13,17,20,22,23,25 Of course, the limited sample size of our series could imply a significant risk of false negative results in the analysis of single prognostic factors.…”
Section: Discussionmentioning
confidence: 95%
“…Several prospective and retrospective studies showed that a higher number of Ra-223 cycles is associated with survival advantage, demonstrating a significant decrease in median OS in patients who received 1 to 4 compared to patients treated with 5 or 6 Ra-223 administrations. 45,22 In the ALSYMPCA trial the median OS was 17.9 months in patients who received 5 or 6 Ra-223 administrations and 6.2 months in those treated with 1 to 4 administrations. 2 In the iEAP the median OS was 6.3 months in patients receiving less than 5 cycles compared to more than 16 months in those treated with 5 or 6 cycles.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations